Resilience Promotion Model of Elderly with Chronic Diseases and Depression by Integrating the Goal Attainment Theory - ทองคุ้ม, กนกภรณ์; พึ่งโพธิ์สภ, นริสรา; สกุลพงศ์, นันท์ชัตสัณห์ (Journal of Health Science of Thailand, 2022)
The objective of this action research was to develop a model of resilience promotion among the elderly with chronic diseases with depression by integrating the goal attainment theory. Data were collected by focus group discussion, observation, and the Resilience Scale for the elderly with chronic diseases with depression. The data were analyzed with content analysis, mean, and standard deviation. The main informants were 12 elderly people with chronic diseases and depression who lived in Khaibangrachan District in Singburi Province. The secondary informants were 4 village health volunteers. The first cycle of the study was conducted to study the situation of resilience promotion and experimenting with a resilience promotion program by integrating the goal attainment theory. Cycle 2 applied the modified program and evaluated the effectiveness of the program. The study results found that elderly people with chronic diseases with depression understand the meaning and components of resilience. They could use their signature strengths to increase their emotional stability when facing problems, looked at the problem by optimism, and asked for help from the good things that exist around in order to encourage them to pass problems and obstacles. After participating the program, the elderly with chronic diseases and depression had higher mean scores on Resilience Scale (Mean=90.33, SD=7.17) than before participating in the program (Mean=56.58, SD=4.77). Thus the development of a model of resilience promotion among the elderly with chronic diseases and depression was successful through the integration of the goal attainment theory, consisting of 5 activities: (1) strengthening willpower with friendship, (2) persist through problems, (3) overcoming problems in positive manner, (4) good things that were valuable to me, and (5) my resilience.